IN VITRO CEFIXIME DISSOLUTION IN PHARMACOPEIA-RECOMMENDED MEDIUM AND SIMULATED GASTROINTESTINAL FLUIDS: A COMPARATIVE STUDY - ANES AM THABIT; AHMED MS AL-GHANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of this study was to compare in vitro dissolution of cefixime in a pharmacopeial-recommended medium and in simulated gastrointestinal fluids. Methods: Before dissolution testing, the drug content in the tested materials was determined by ultraviolet spectrophotometer. The dissolution media used in this study were recommended by the United States Pharmacopeia (USP) as well as four different media that mimic gastric and intestinal fluids in fed and fasted states. The tested materials included the pure drug and two 0.2-g capsule brands (original and test). Results: The pharmacopeial medium showed no difference in both extent and rate of the drug dissolution between the tested materials. In the contrary, the difference was significant when the simulated fluids were used. Moreover, it was found that the simulated intestinal fluid (SIF) of fed state showed 21–32% decrement in the drug dissolution compared to that of the corresponding fasted-state simulated fluid. Indeed, this finding agreed those of in vivo bioavailability studies published in literature. Conclusion: The SIF is much more valid as a medium for in vitro testing of cefixime capsule than the one recommended by the USP.